2010
DOI: 10.1007/s10533-010-9519-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon and litter development along a reconstructed biodiverse forest chronosequence of South-Western Australia

Abstract: Soil organic matter (SOM) increases with time as landscape is restored. Studying SOM development along restored forest chronosequences would be useful in clarifying some of the uncertainties in quantifying C turnover rates with respect to forest clearance and ensuing restoration. The development of soil organic matter in the mineral soils was studied at four depths in a 16-year-old restored jarrah forest chronosequence. The size-separated SOM fractionation along with d 13 C isotopic shift was utilised to resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
2
17
1
Order By: Relevance
“…George et al . () observed organic matter accumulated in the topsoil with increasing time since restoration, which was a trajectory towards a native soil carbon profile. We found nitrate and phosphorous decreased with age of restoration, which is also consistent with previous trends from the restoration of abandoned pastoral lands (Cunningham et al .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…George et al . () observed organic matter accumulated in the topsoil with increasing time since restoration, which was a trajectory towards a native soil carbon profile. We found nitrate and phosphorous decreased with age of restoration, which is also consistent with previous trends from the restoration of abandoned pastoral lands (Cunningham et al .…”
Section: Discussionmentioning
confidence: 78%
“…The direction of this change was towards the concentrations found at the remnant sites, which appears consistent with a previous study of Jarrah forest restoration in Western Australia (George et al . ). George et al .…”
Section: Discussionmentioning
confidence: 97%
“…Contrary to our hypothesis, we did not observe significant increases of SOM, TC, or TN along with increasing WRP age at each depth. George et al (2010) obtained a slight increasing trend of TC along a restored forest chronosequence in southwestern Australia, although TC contents were not significantly different among restoration ages. The unit of soil carbon in mass was often translated to volume to eliminate the effect of soil management on compaction.…”
Section: Resultsmentioning
confidence: 96%
“…Currently only anecdotal evidence exists to support this proposition (Tibbett, 2008, Tibbett, 2010and George et al, 2010. George et al (2010) studying the variation in the stable isotopic soil carbon (δ 13 C) signature following de novo establishment of diverse vegetation in post-mined restored landscapes of South-Western Australia revealed that with increasing forest age (productivity) there was a re-establishment of the labile to refractory carbon continuum with soil depth which was comparable to undisturbed native forest (Fig.…”
Section: A Synergistic Approach To Carbon Sequestration and Biodiversitymentioning
confidence: 99%